Perlindungan Data Pribadi Pada Platform Digital Pinjaman Online Ditinjau Dari Undang-Undang Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi (Studi Kasus Di Kota Kupang, NTT) - Kim, Maria Theresia; Jacob, Yossie M Y; Dju Bire, Chatryen M (Law Faculty, Nusa Cendana University, 2025)
The protection of personal data on online lending digital platforms has become an increasingly important issue in line with the rapid development of information and communication technology. This study aims to analyze the legal protection of personal data in the context of online lending in Kupang City, East Nusa Tenggara, with reference to Law Number 27 of 2022 concerning Personal Data Protection (UU PDP). The research method used is empirical law, with data collection through interviews and literature studies. The results show that although the PDP Law provides a clear legal framework, there are still weaknesses in its implementation, especially related to public awareness of their rights to personal data. Factors causing personal data leakage include internal weaknesses in data management by online loan providers, as well as external factors such as economic conditions and lack of education. This research recommends the need for a comprehensive approach that combines preventive and repressive efforts to improve personal data protection, as well as raising public awareness of the importance of data security. Thus, it is hoped that the protection of personal data can be guaranteed, support public trust, and encourage sustainable growth of the digital economy.